PERANCANGAN ALAT MONITORING KECEPATAN ANGIN MENGGUNAKAN ARDUINO UNO - Zahra, Elza Maudy; Fajrin, Alfannisa Annurullah (LPPM Universitas Putera Batam, 2024)
In studying the field of Meteorology and Geophysics, monitoring wind speed is very useful for human activities such as activities related to transportation. Excessive wind speed can hinder fishermen from carrying out their work when they want to catch fish at sea and hinder fish drying activities when there is strong wind. The lack of digital activity or availability of smartphones also makes it difficult for fishermen to find out the current wind speed, such as through wind monitoring applications so that fishermen only see wind speed based on the movement of objects around them that are blown by the wind. In this regard, a tool is needed to measure wind speed called an anemometer along with its monitoring to produce information about how much wind speed is occurring in the surrounding environment. This wind speed monitoring tool can find out how much wind speed is occurring. The design of this wind speed monitoring tool uses an Arduino Uno as a microcontroller, an I2C LCD to display information about the wind speed, an anemometer sensor which functions as a sensor that will measure wind speed, the results of which will be displayed via the I2C LCD in real-time.